Intrauterine instillation of diluted seminal plasma at oocyte pick-up does not increase the IVF pregnancy rate: a double-blind, placebo controlled, randomized study - Wolff, Michael von; Rösner, Sabine; Germeyer, Ariane; Jauckus, Julia; Griesinger, G.; Strowitzki, Thomas (Human reproduction, 2013)
Does intrauterine application of diluted seminal plasma (SP) at the time of ovum pick-up improve the pregnancy rate by ≥14% in IVF treatment?Intrauterine instillation of diluted SP at the time of ovum pick-up is unlikely to increase the pregnancy rate by ≥14% in IVF.SP modulates endometrial function, and sexual intercourse around the time of embryo transfer has been suggested to increase the likelihood of pregnancy. A previous randomized double-blind pilot study demonstrated a strong trend towards increased pregnancy rates following the intracervical application of undiluted SP. As this study was not conclusive and as the finding could have been confounded by sexual intercourse, the intrauterine application of diluted SP was investigated in the present trial.A single-centre, prospective, double-blind, placebo-controlled, randomized, superiority trial on women undergoing IVF was conducted from April 2007 until February 2012 at the University Department of Gynaecological Endocrinology and Reproductive Medicine, Heidelberg, Germany.The study was powered to detect an 14% increase in the clinical pregnancy rate and two sequential tests were planned using the Pocock spending function. At the first interim analysis, 279 women had been randomly assigned to intrauterine diluted SP (20% SP in saline from the patients' partner) (n = 138) or placebo (n = 141) at the time of ovum pick-up.The clinical pregnancy rate per randomized patient was 37/138 (26.8%) in the SP group and 41/141 (29.1%) in the placebo group (difference: −2.3%, 95% confidence interval of the difference: −12.7 to +8.2%; P = 0.69). The live birth rate per randomized patient was 28/138 (20.3%) in the SP group and 33/141 (23.4%) in the placebo group (difference: −3.1%, 95% confidence interval of the difference: −12.7 to +6.6%; P = 0.56). It was decided to terminate the trial due to futility at the first interim analysis, at a conditional power of 62%.The confidence interval of the difference remains wide, thus clinically relevant differences cannot reliably be excluded based on this single study.The results of this study cast doubt on the validity of the concept that SP increases endometrial receptivity and thus implantation in humans.Funding was provided by the department's own research facilities.DRKS00004615.
Gesehen am 16.09.2021